Artificial fertilization in turbot, Scophthalmus maximus (L.): different methods and determination of the optimal sperm-egg ratio - Chereguini-Fernández-Maquieira; María del Olvido; García-de-la-Banda, Inés; Rasines, Inmaculada; Fernández-Lamas, José Ángel (1999)
Sí